2021
DOI: 10.1002/adhm.202002103
|View full text |Cite
|
Sign up to set email alerts
|

Fast Stereolithography Printing of Large‐Scale Biocompatible Hydrogel Models

Abstract: Large size cell-laden hydrogel models hold great promise for tissue repair and organ transplantation, but their fabrication using 3D bioprinting is limited by the slow printing speed that can affect the part quality and the biological activity of the encapsulated cells. Here a fast hydrogel stereolithography printing (FLOAT) method is presented that allows the creation of a centimeter-sized, multiscale solid hydrogel model within minutes. Through precisely controlling the photopolymerization condition, low suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…It should be noted that, in the proof-of-concept prints reported in our study, perfusion was demonstrated via manual injection, recent reports in the literature highlight elegant strategies for enabling the connection of hydrogel-based constructs to fluidic tubing and circuits, which could be applied to automate fluid flow [ 66 ]. To date complex and branched omnidirectional network of channels have been reported via lithographic printing mainly in stiff synthetic hydrogel, most commonly PEGDA [ 15 ] or GelMA and PEGDA blends [ 28 , 67 ], which result in dense networks that limit the range of applications to tissues or models in which cell migration is not needed [ 68 ]. Gelatin-only hydrogels, although widely investigated in the field of biofabrication, have been mainly processed to form channels with planar geometries [ 16 , 59 , [69] , [70] , [71] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, in the proof-of-concept prints reported in our study, perfusion was demonstrated via manual injection, recent reports in the literature highlight elegant strategies for enabling the connection of hydrogel-based constructs to fluidic tubing and circuits, which could be applied to automate fluid flow [ 66 ]. To date complex and branched omnidirectional network of channels have been reported via lithographic printing mainly in stiff synthetic hydrogel, most commonly PEGDA [ 15 ] or GelMA and PEGDA blends [ 28 , 67 ], which result in dense networks that limit the range of applications to tissues or models in which cell migration is not needed [ 68 ]. Gelatin-only hydrogels, although widely investigated in the field of biofabrication, have been mainly processed to form channels with planar geometries [ 16 , 59 , [69] , [70] , [71] ].…”
Section: Resultsmentioning
confidence: 99%
“…A particular attention was directed towards designing a system to enable prints with high shape fidelity microchannels, even when using hydrogels displaying very low stiffness (∼1 ​kPa). Such system would overcome the current limitations experience in the field of DLP (bio)printing, which is mostly reliant on stiff high polymer content materials [ 28 ], and thus can open new opportunities for material scientists, engineers and biologists to build the next generation of 3D constructs with ideal properties for cell encapsulation, tissue engineering and regenerative medicine. The DLP working curve for the low-temperature soluble gelatin-based bioresins, exposure settings and printing resolution were described as a function of crosslinking chemistry and the polymer concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] PVDF (polyvinylidene fluoride), a polymer with great piezoelectric properties, was found to have sufficient Young's modulus and toughness needed for compressive buckling (Figure S4, Supporting Information). [ 46 ] In contrast, PLGA (50:50) alone has high mechanical modulus but low ductility, making it too brittle to undergo the buckling process (Figure S3, Supporting Information). [ 47 ] Based on the material characterization performed in the current study, a toughness higher than 3 MPa seems to be sufficient for the compressive buckling process.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of GelMA: GelMA was synthesized following previous publications. [46,51] Briefly, methacrylic anhydride (Sigma, 276 685) was added dropwise to a 10% solution of gelatin (Sigma, G1890) in PBS at the weight ratio of methacrylic anhydride: gelatin = 3: 5 under constant stirring, and react at 50 °C for 1 h. The functionalized polymer was dialyzed against distilled water for 7 days at 40 °C to remove methacrylic acid and anhydride, and neutralized to pH 7.4. Final freezedried GelMA product was gathered, dissolved in PBS at concentration of 25% (w/v), and stored in freezer at −20 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Embedded vascular networks present a more immediate route to achieving blood flow through engineered tissues than the protracted process of microvascular invasion and anastomosis (11). Indeed, an expanding suite of 3D printing technologies encompassing embedded extrusion printing (12,13), hydrogel stereolithography (14), and sacrificial templating (15)(16)(17)(18) now permit the generation of model tissues pervaded by extensive networks of perfusable channels, which can also serve as a substrate for seeding of an endothelial monolayer. In particular, hierarchical vascular trees with a single inlet and outlet have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%